2016
DOI: 10.1111/oik.03712
|View full text |Cite
|
Sign up to set email alerts
|

Fine with heat, problems with water: microclimate alters water loss in a thermally adapted insular lizard

Abstract: Global change, including habitat isolation and climate change, has both short‐ and long‐term impacts on wildlife populations. For example, genetic drift and inbreeding result in genetic impoverishment in small, isolated populations, while species undergo range shifts or adaptive phenotypic change in response to shifts in environmental temperatures. In this study, we utilize a model system in which Holocene landscape changes have occurred to examine long‐term effects of population isolation. To examine how isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 70 publications
4
29
1
1
Order By: Relevance
“…Our 30-yr study supports the hypothesis that water availability rather than climate warming will be the limiting factor in (nocturnal) desert reptiles though nevertheless temperature was observed to be important but not limiting in almost all lifehistory processes. In line with our findings, other studies provided evidence that both rainfall and temperature affect lizards in various ways with water availability being a stronger driver than temperature in most of the ecological processes (Pianka 1986, Smith et al 1995, Read et al 2012, Garc ıa-Muñoz and Carretero 2013, Belasen et al 2016, Rotger et al 2016. Also, our results highlight the need to account not only for physiological constraints such as CTmax for drawing conclusions about the effect of climate change, but also to consider behavioral adjustments, phenotypic plasticity, and ecological responses that can balance the effect of temperature, for instance, through water availability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our 30-yr study supports the hypothesis that water availability rather than climate warming will be the limiting factor in (nocturnal) desert reptiles though nevertheless temperature was observed to be important but not limiting in almost all lifehistory processes. In line with our findings, other studies provided evidence that both rainfall and temperature affect lizards in various ways with water availability being a stronger driver than temperature in most of the ecological processes (Pianka 1986, Smith et al 1995, Read et al 2012, Garc ıa-Muñoz and Carretero 2013, Belasen et al 2016, Rotger et al 2016. Also, our results highlight the need to account not only for physiological constraints such as CTmax for drawing conclusions about the effect of climate change, but also to consider behavioral adjustments, phenotypic plasticity, and ecological responses that can balance the effect of temperature, for instance, through water availability.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that other similar reptile species will likely encounter similar limitations. Notwithstanding, responses to changing climate can differ remarkably among (Dickman et al 1999, Letnic et al 2004, Read et al 2012) and within species (Bestion et al 2015, Belasen et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The former intrapopulation sample size is within the range of that used in many studies of lizard thermal tolerance (e.g., Beal, Lattanzio, & Miles, ; Muñoz et al., ). However, we assessed optimal sample size from six datasets, including population CT max from 8 to 25 adult lizards from the Americas, Asia and Europe (Andrango, Sette, & Torres‐Carvajal, ; Belasen et al., ; Buckley, Ehrenberger, & Angilletta, ; Huang & Tu, ; Muñoz et al., ; and unpublished data), and concluded that a sample size of three males should accurately capture the mean population CT max estimated from larger population sizes (Supporting Information Table S2; Figures S4–S9).…”
Section: Methodsmentioning
confidence: 99%
“…These PVC T e models have been calibrated against live lacertid lizards of similar size to P. husabensis (Belasen et al. ; R 2 = 0.84, slope not significantly different from 1 and intercept not significantly different from zero). We compared the copper and PVC models by deploying both next to each other in P. husabensis habitat and left them for 15 d (24 June–8 July 2014) recording temperatures every 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…To incorporate our data into the modeling framework of Sinervo et al (2010), we followed their standard protocol and measured operative environmental temperatures (Hobo data loggers U23-003; Onset Computer) using models constructed from standardized hollow, empty, capped polyvinyl chloride (PVC) pipes (80 mm 9 15 mm, 1 mm wall thickness) spraypainted primer gray (NEO Dur semi-matt acrylic emulsion, Pastel Base, WOT, 1 L mixed with 100 mL NEO Charcoal 122, Windhoek, Namibia). These PVC T e models have been calibrated against live lacertid lizards of similar size to P. husabensis (Belasen et al 2017; R 2 = 0.84, slope not significantly different from 1 and intercept not significantly different from zero). We compared the copper and PVC models by deploying both next to each other in P. husabensis habitat and left them for 15 d (24 June-8 July 2014) recording temperatures every 10 min.…”
Section: Extinction Risk Modelingmentioning
confidence: 99%